Waterborne Virus Transport and Risk Assessment in Lake Geneva Under Climate Change - Chaojie Li; Tamar Kohn (Earth's Future, 2024)
Abstract Climate changes influence lake hydrodynamics and radiation levels and thus may affect the fate and transport of waterborne pathogens in lakes. This study examines the impact of climate change on the fate, transport, and associated risks of four waterborne viruses in Lake Geneva. We used a coupled water quality‐microbial risk assessment model to estimate virus concentrations and associated risks to recreational water users for each month in 2019 and 2060. Long‐term hydrodynamic simulations suggested that although the annual hydrodynamic transport pattern of Lake Geneva will remain relatively stable, a 1.9°C increase of lake surface water temperature can be expected, while a slight decrease in lake current velocity may occur. The subsequent effect on the fate and transport of the four enteric viruses was found to vary by time of year. During warmer periods, the increase of virus inactivation due to higher water temperature and stronger solar radiation at the earth's surface will compensate for the additional virus discharge brought about by population growth over the time period considered, whereas during winter the virus concentration near the lake shore and the associated infection probabilities risks are likely to increase due to population growth. Additionally, the current estimation of virus inactivation rate shows significant variability, which has a more substantial effect on enteric virus concentrations in the lake compared with changing climate parameters. Overall, the study suggests that future risks posed by enteric viruses with recreational water users near popular beaches around Lake Geneva will likely remain similar to current risks and accurate estimation of the environmental inactivation of viruses is crucial for predicting the fate of enteric viruses in the aquatic system.